MICROSOFT ACCESS APPLICATION SUPPORT AS MAKING TAPE AND COMPACT DISK CATALOGING IN PT. SUARA TUNGGAL ANGKASA RAYA - Enung Mariam; Ir. Fitri Sjafrina, MMSI (Jurnal Sistem Informasi, 2000)
Increasing number of private radio stations today, spur competition in improving thequality of the radio station. One is the format of the show, a radio star who has theformat of the show playing the songs in the form desired by the listener, to facilitatethe implementation of the screening officer within the song, the writer assists them inmaking cassette and compact disk catalog. With the aim of presenting information tostakeholders about the layout of cassettes and compact disks.Before you create a catalog, first cassettes and compact disks are grouped accordingto the Dewey classification tithing, through microsoft access software application.Currently preparing a cassette and a compact disc is grouped by type of music and asinger, as well as placed on the shelf placement of cassette tapes that have not beenfilled (empty) with the type of music.